(untitled) (Manila, Philippines, 2004)
Contents: ADB and the cities alliance; Urban growth and poverty in the region; Institutionalizing the city development strategy; Integrating CWS programs...
Keywords: City planning,Phát triển thành phố; Asia,Châu Á